NEUTRAL ARROW STATUS AND DETERMINATION OF SECTION NUCLEUS (Academicia Globe: Inderscience Research, 2022)
The structural elements used in construction are required to be durable for a long time, without losing their strength, durability and priority under the influence of external forces.  The article provides recommendations for methods for determining the neutral axis and the cutting core formed in the sections of parts that resist elongation, compression or bending in technical structures and construction areas.